Microfinance Failures: the Case of Microfinance in West African Economic and Monetary Union - Edith L. Togba; Simon Alain Song Ntamack (European Scientific Journal, ESJ, 2019)
This paper investigates on the determinants of MFIs’failure in WAEMU. It carries out the analysis on the panel data from 2000-2014 by estimating logit regression of this probability. It reveals that the driven factors of the probability of being unsustainable for these institutions are related to the poor risk management and the poor management of the operating expense. These factors are administrative expense ratio and Portfolio at risk for more than thirty days that have a positive effect on this probability. At a lower level, the depth of financial system has also a positive effect. Some factors such as Equity, portfolio yield, and the MFIs type (NGOs and Credit Union) have a negative effect on the probability of being unsustainable. One of the main findings is related to the indicators of outreach used here. In effect, the size of loan and the number of borrowers influence negatively and significantly the probability of failure.